Nickel-catalyzed fluoroethylation of arylboronic acids via Suzuki-type coupling. Issue 9 (22nd March 2019) - Yang, Yi; Cai, Junjie; Luo, Gen; Jiang, Yan; Su, Yumei; Su, Yang; Li, Chaolin; Zheng, Yubin; Zeng, Jijiao; Liu, Yingle
Abstract : A new and step-economic method for the synthesis of homobenzylic fluorides through nickel-catalyzed Suzuki-type fluoroethylation coupling is developed. Abstract : A mild method for efficient access to fluoroethylated (hetero)arenes via Suzuki-type coupling has been developed. This base metal Ni-catalyzed method features selective transformation of the more susceptible C–X bond of 1-fluoro-2-haloethanes (FCH2 CH2 X, X = I or Br) and leaves the vicinal fluorine intact. Preliminary mechanistic studies illustrate the intermediacy of fluoroethyl radicals in the radical-rebound oxidative addition and Ni–B transmetalation as the rate-limiting step within the catalytic cycle. The practical value of this protocol is further demonstrated by late-stage modification of several complex bioactive molecules.